Produção de quitinases e biossurfactantes fúngicos por processos fermentativos - Reis, Cristiane Bianchi Loureiro dos (2017)
Brazil's agricultural growth is based on the use of large quantities of synthetic agrochemicals, which result in high production costs and environmental degradation. On the other hand, Brazil harbors the greatest biodiversity on the planet and the non-predatory use of this resource can contribute to obtaining bioproducts for use in more sustainable agricultural systems. Thus, the aim of the thesis is to obtain chitinases and biosurfactants from the optimized culture in bioreactors of microorganisms, aiming the development of bioinsecticides and bioadjuvants for agricultural use. Chitinase production by the fungus Metharizium anisopliae was optimized in solid fermentation medium containing sugarcane bagasse as a substrate. The influence of the variables chitin mass, temperature and humidity was evaluated through a rotational central composite design, resulting in a maximum chitinolytic activity of 6.78 U g-1, indicating that it is possible to increase the scale of chitinase production in bioreactors. The fungi producing biosurfactants were isolated from the soil of the Pampa Biome. After selection, the most promising isolate was identified by molecular biology techniques as being of the species Fusarium fujikuroi. To optimize the production of a biosurfactant, a Plackett-Burman matrix was used to evaluate the pH, temperature, agitation, inoculum quantity and incubation period in the submerged fermentation medium containing glucose as the carbon source. The biosurfactant activity was detected by the surface tension of the growth medium, which was reduced from 72 mN m-1to 28.04 mN m-1 in the best condition. The results obtained so far demonstrate the potential of F. fujikuroi for the optimization of the scaling up of biosurfactant production in bioreactors. Physical-chemical analysis of the biosurfactant will also be performed and the ability to reduce surface tension in formulations with insecticides will be evaluated